TOR-TOR SIRINTAK HOTANG PADA MASYARAKAT SIMALUNGUN KAJIAN TERHADAP KONSEP KOREOGRAFI - Irma Botorani Gultom Botorani Gultom (Gesture: Jurnal Seni Tari, 2013)
Hotang sirintak Tor-tor dance is a dance that originated from the movement area Simelungun looking for rattan to describe the activities of the forest . The purpose of the research is to discuss the composition of range of motion tor-tor sirintak Hotang , background preparation tor-tor sirintak hotangberdasarkan Batak Simelungun philosophy and application tor - tor koreografitor sirintak Hotang based accompaniment patterns . Theories used in conjunction with a research topic that is understanding sirintak Hotang tor-tor , choreography theory , philosophy Batak Simelungun and accompaniment patterns . Time is used to discuss research on tor - tor sirintak Hotang on the study of the concept of choreography Simelungun done for 2 month,  at the end of June 2013 to August 2013. Research site is in District Simalungun Kingdom . The population in this study is a community that knows Simelungun tor-tor sirintak Hotang , artists and dancers , the sample in this study is a part of the population , the artists and dancers who know about tor - tor sirintak Hotang . Data collection techniques include observation , interviews , library research and documentation , which are then analyzed with descriptive qualitative method . Based on the research that has been done, the concept of choreography Tor-tor dance sirintak Hotang which contains noble values ​​habonaron do bona philosophy Simelungun Society. Tor-tor sirintak Hotang has external music accompaniment, the music that was born from the outside of the human body or the use of musical instruments which means it is the accompaniment of dance accompanied by live musicians using a set of musical instruments namely gonrang sipitu-pitu, sarunei, ogung and mongmongan. The music used is the traditional music that is imbou manubung Simelungun .